Phytochemical-Based Nanomedicine for Advanced Cancer Theranostics: Perspectives on Clinical Trials to Clinical Use - Dhupal M (Dove Medical Press, 2020)
Madhusmita Dhupal,1 Devasish Chowdhury2 1Department of Microbiology, Wonju College of Medicine, Yonsei University, Wonju 26426, Republic of Korea; 2Material Nanochemistry Laboratory, Physical Sciences Division, Institute of Advanced Study in Science and Technology, Guwahati 781035, IndiaCorrespondence: Devasish ChowdhuryMaterial Nanochemistry Laboratory, Physical Sciences Division, Institute of Advanced Study in Science and Technology, Paschim Boragaon, Garchuk, Guwahati 781035, IndiaTel +91 361 2912073Fax +91 361 2279909Email devasish@iasst.gov.inMadhusmita Dhupal Department of Microbiology, Wonju 26426, Republic of KoreaEmail dhupal25@gmail.comAbstract: In the current chapter, a new strategic compilation of phytochemicals with potent antitumor properties has been addressed, most importantly focusing on cell cycle arrest and apoptotic signaling mechanism. A promising approach in tumor prevention is to eliminate cancer cells preferably via cell cycle arrest and programmed cell death with lesser harm to neighboring normal cells. Cancer cells have a survival advantage to escape apoptosis and relentlessly divide to proliferate, gearing up the cell cycle process. Recently, the use of phytochemical-derived conjugated chemotherapeutic agents has increased dramatically owing to its biocompatibility, low cytotoxicity, low resistance, and dynamic physiochemical properties discriminating normal cells in the treatment of various cancer types. For decades, biomedical investigations have targeted cell cycle and apoptotic cell death mechanism as an effective cancer-killing tool for systemically assessing the potential biological interactions of functional phytocompounds compared to its synthetic counterparts during their complete life cycles from entry, biodistribution, cellular/molecular interactions to excretion. Newly emerging nanotechnology application in anticancer drug formulations has revolutionized cancer therapy. Tissue-specific phyto-nanomedicine plays a vital role in advanced cancer diagnostics using liposome, micelle, and nanoparticles as a precise and effective delivery vehicle. This chapter specifically focuses on the therapeutic phytomolecules approved by the Food and Drug Administration (FDA, USA) along with phyto-chemopreventives currently on clinical trials (Phase-I/II/III/IV). Besides, detailed coverage is given to the FDA-approved nanotechnology-based formulations only in the areas of cancer theranostics via cell cycle arrest and apoptotic pathways including present challenges and future perspectives.Keywords: phytochemicals, cancer therapeutics, apoptosis, cell cycle arrest, chemo-preventive agents, clinical trials